Analysis Of Multiple Hole Structures Of Basalt Epoxy Laminates - Daran, Vivegan Murali (IRC, 2017)
Multiple holes in different patterns are present on these composite structures for fastening purposes. The presence of holes in a structure results in a high stress gradient at the vicinity of their edges. Unlike isotropic materials, the stress gradient around a hole in a laminated composite is not only dependent on material properties, but also on fibre orientation and laminate stacking sequence. This complex stress gradient results in a complicated failure mechanism near the hole. This study is conducted to investigate the tensile strength and flexural strength of basalt/epoxy laminates, as well as to determine the effects of different hole configurations on the strength of basalt epoxy composite laminates. Basalt laminates were prepared using hand lay-up technique with ply orientation of zero degrees and fibre mass fraction of 60%, using epoxy resin as matrix. The hole sequences of the laminates are zero hole (intact specimen), single hole and two holes (vertical and horizontal array). ASTM standards D3039M and D790 were used for tensile test and flexural test respectively. Finite element simulations were conducted in an attempt to provide validation for the mechanical tests. The results reveal that the strength of the basalt laminates is the highest with the intact specimen and the lowest with two holes in a horizontal arrangement, while specimens with single hole and two holes in vertical array were both stronger than the latter. Specimens with two holes in vertical array had elastic moduli 5.48% lower compared to the intact specimen in the flexural test results. For tensile loading, the percentage difference in elastic modulus was 14.25% between single hole specimen and the intact specimen. Data and other findings from this study could be helpful in providing better understanding of the effects of holes made for fastening purposes on the composite structures.